New records of Anthalona acuta Van Damme, Sinev & Dumont 2011 and Anthalona brandorffi (Sinev & Hollwedel, 2002) in Brazil, with description of a new species of the simplex-branch (Crustacea: Cladocera: Chydoridae) - Sousa, Francisco Diogo R.; Elmoor-Loureiro, Lourdes M.A.; Debastiani-Júnior, José Roberto [UNESP]; Mugnai, Riccardo; Senna, André (Magnolia Press, 2015)
The range of geographical distribution of Anthalona acuta Van Damme, Sinev & Dumont 2011 and Anthalona brandorffi (Sinev & Hollwedel, 2002) in Brazil has increased by almost 2000 km to the south. New records of Anthalona verrucosa verrucosa (Sars, 1901) were also added. Populations of Anthalona brandorffi from Central Brazil showed a peculiar mor-phological variation, with some individuals having only a single denticle on the labral keel. A new species of the simplex-branch, Anthalona neotropica sp. Nov., was described based on Brazilian material, and this is the first taxon of this branch registered in the Neotropics. It differs from Anthalona simplex Van Damme, Sinev & Dumont 2011, a Central African species, in the morphology of underneath sack of the lateral head pores, length of IDL setae and armature of first flaming-torch seta of limb IV. It could be distinguished from Anthalona sanoamuangae Sinev & Kotov, 2012 (distributed through the South- East Asia) by the morphology of the main head pores, length of IDL setae and armature of the pecten of post-abdominal claw. Anthalona neotropica sp. Nov. seems to have a benthic/hyporheic habit. All studied species have a wide geographical distribution and could be confused with Anthalona verrucosa Sars, 1901, thus at least some if not all previous records of this species on the continent must be revised.
Keywords: Anomopoda; Anthalona verrucosa; Geographical distribution; Head pores; Taxonomy; Terminal claw